2020
DOI: 10.15537/smj.2020.10.25390
|View full text |Cite
|
Sign up to set email alerts
|

Taxation and tobacco plain packaging effect on Saudi smokers quitting intentions in Riyadh city, Saudi Arabia

Abstract: Objectives: The current research aims to study the impact of raising tobacco tax and implementation of plain packaging on male smokers' quitting intentions in Saudi Arabia. Methods: The study adopts a quantitative approach where close-ended questionnaires are distributed among 1,015 male participants from different regions of Riyadh city, Saudi Arabia. Bivariate analysis and logistic regression analysis are conducted using SPSS software to analyze the collected primary data. Results: The study found a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…29 Our result is consistent with studies published in 2020 and 2021 indicating that no association was observed between education and intention to quit smoking. 7,29,34 Our estimates of price elasticity of demand corresponded with the changes in taxation policy that increased prices. The positive elasticity figures for the years from 2013 to 2015 were not in alignment with the goals of WHO and the World Bank to reduce consumption by increasing prices.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…29 Our result is consistent with studies published in 2020 and 2021 indicating that no association was observed between education and intention to quit smoking. 7,29,34 Our estimates of price elasticity of demand corresponded with the changes in taxation policy that increased prices. The positive elasticity figures for the years from 2013 to 2015 were not in alignment with the goals of WHO and the World Bank to reduce consumption by increasing prices.…”
Section: Discussionmentioning
confidence: 74%
“… 18 A cross-sectional study using a quantitative research approach among 1015 male participants from 2018 to 2020 in Riyadh revealed no significant association between income and intention to quit. 34 This disparity in results requires more national research to explore the correlation between income and cigarette consumption in addition to in-depth studies about the socioeconomic determinants of smoking in Saudi Arabia. We also found a strong inverse correlation between unemployment and tobacco use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the included studies were conducted in Australia 32,36–38,40,43. Most of the studies involved only the adult age group 29,31,34,36–38. Only 2 studies involved only the adolescent age group 30,39.…”
Section: Resultsmentioning
confidence: 99%